Hubungan antara Ekspresi p63 dengan Jenis Histopatologis Penderita Kanker Serviks Stadium IB2 dan IIA - D.L.T, MARINGAN (Indonesian Journal of Cancer, 2014)
HPV is known the main etiology of cervical cancer, through its E6 and E7 oncogenes that inactivate p53 and retinoblastoma protein, thus suggested as the mechanism of phenotype changes. As the p53 homologs was found, p73 and p63, study focusing on p53 is more complex. Analysis of p63 expression by immunohistochemistry has prognostic and predictive value on several tumor types. P63 has main role on stratified epithelial growth by maintaining proliferation and differentiation. This study was analytic observational with cross sectional design. All subjects underwent cervical biopsy and were analyzed for p63 expression by immunohistochemistry. Statistical analyze used in this study were chi square and Mann Whitney. This study has been approved by the institution ethical committee. We found no significant correlation between subjects characteristic (age, marital age, parity) and clinical stage of cervical cancer (p>0.05). Our samples consisted of 25 squamous cell carcinoma (64%), 11 adenocarcinoma (28%), and 3 adenosquamous carcinoma (8%). Expression of p63 had no correlation with clinical stage, however its nuclear expression was significantly higher on squamous carcinoma type (72%) compared to adenocarcinoma (11%), with p < 0.001. Conclusion: expression of p63 on squamous cell carcinoma cervix is significantly higher compared to adenocarcinoma or adenosquamous.